Water-absorbent resin composition, water stop material, and cable
By combining the water-absorbent resin particles and the phosphonic acid-based chelating agent, a water-absorbent resin composition with excellent heat resistance is solved, and the problem of insufficient heat resistance after swelling in the prior art is solved, and stable water-stopping performance in a high-temperature environment is achieved.
Patent Information
- Application Number
- CN202380066830.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-22
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-25
AI Technical Summary
The water-absorbent resin used in the existing water-stopping materials is insufficient in heat resistance after swelling, and it is prone to deteriorate due to heat generated by the cable, which affects the water-stopping performance.
By combining the water-absorbent resin particles and the phosphonic acid-based chelating agent in a predetermined ratio, a water-absorbent resin composition with excellent heat resistance is formed. The composition can maintain high viscosity in a swelling state and reduce gel deterioration.
The swelled water-absorbent resin composition has excellent heat resistance, can maintain the stability and water-stop properties of the gel under high temperature environment, and is suitable for use in cables and other applications.
Smart Images

Figure FT_1 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a water-absorbent resin composition, a water-stopping material and a cable. Background Art
[0002] It is known that water-absorbent resins have excellent water absorption capacity and can exhibit water-stopping effects, and therefore can be used in various applications requiring water-stopping properties. For example, water-absorbent resins are used as water-stopping materials for communication cables such as optical cables and power cables.
[0003] Patent Document 1 discloses a technique in which a water-stopping material is formed by enclosing a water-absorbent sheet containing a water-absorbent resin in an exterior material to prevent the gel of the water-absorbent resin that swells after absorbing water from seeping out.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-147281 Summary of the invention
[0007] Problems to be solved by the invention
[0008] For the water-absorbing resin used in the above-mentioned water-stopping material (for example, water-stopping strip), in addition to having a swelling property (water-stopping property) that can immediately prevent water intrusion, it is also important to have excellent heat resistance even after swelling, that is, the gel (water-absorbing resin after swelling) is not easily deteriorated by the heat generated by the cable.
[0009] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a water-absorbent resin composition having excellent heat resistance after swelling, and a waterproof material and a cable containing the composition.
[0010] Methods used to solve problems
[0011] The present inventors have conducted intensive studies to achieve the above object and have found that the above object can be achieved by combining water-absorbent resin particles and a phosphonic acid chelating agent in a predetermined ratio, thereby completing the present invention.
[0012] That is, the present invention includes, for example, the subject matters described in the following items.
[0013] Item 1
[0014] A water-absorbent resin composition comprising water-absorbent resin particles and a phosphonic acid chelating agent, wherein the phosphonic acid chelating agent is contained in an amount of 0.01 to 40 μmol based on 1 g of the water-absorbent resin particles.
[0015] Item 2
[0016] The water-absorbent resin composition according to Item 1, wherein the 30-second swelling height is 6.0 mm or more.
[0017] Item 3
[0018] A waterproof material comprising the water-absorbent resin composition according to item 1 or 2.
[0019] Item 4
[0020] A cable comprising the water-stopping material described in item 3.
[0021] Effects of the Invention
[0022] The water-absorbent resin composition of the present invention is excellent in heat resistance after swelling. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of a measuring device used to measure the swelling height of a water-absorbent resin composition. DETAILED DESCRIPTION
[0024] The embodiments of the present invention are described in detail below. It should be noted that in this specification, the expressions "comprising" and "including" include concepts such as "comprising", "including", "consisting essentially of", and "consisting only of".
[0025] For the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range in a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range in other stages. For the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can be replaced with the value shown in the embodiment or the value derived unambiguously by the embodiment. In addition, in this specification, the numerical value connected with "~" refers to the numerical range including the numerical value before and after "~" as the lower limit and the upper limit.
[0026] 1. Water-absorbent resin composition
[0027] The water-absorbent resin composition of the present invention comprises water-absorbent resin particles and a phosphonic acid chelating agent, and contains 0.01 to 40 μmol of the phosphonic acid chelating agent per 1 g (=1 gram) of the water-absorbent resin particles.
[0028] The water-absorbent resin composition of the present invention has excellent heat resistance after swelling. That is, the water-absorbent resin composition of the present invention swells inside the cable due to water intruding from the outside when the cable is damaged, and in this swollen state (gel state), it is not easy to cause gel degradation even in a high temperature environment. For example, in the swollen state of the water-absorbent resin composition, even in a high temperature environment, the decrease in gel viscosity of the gel formed by swelling is suppressed compared to conventional water-absorbent resins. Therefore, the water-absorbent resin composition of the present invention can be suitably used in various water-stopping materials, and the water-stopping material is particularly suitable for cable use.
[0029] In the present invention, the quality of the heat resistance of the water-absorbent resin composition can be determined by storing a gel of the water-absorbent resin composition swollen 50 times in an environment at 90°C for a predetermined time and examining the degree of decrease in the gel viscosity during the storage period. Specifically, the heat resistance of the water-absorbent resin composition can be more effectively determined by the measurement conditions described in "Measurement of Gel Viscosity Retention Rate".
[0030] (Water-absorbent resin particles)
[0031] The water-absorbent resin particles contained in the water-absorbent resin composition of the present invention are resins that are swellable in water and are materials that can serve as a main component of the water-absorbent resin composition.
[0032] Among them, the water-absorbent resin particles contained in the water-absorbent resin composition of the present invention particularly preferably have a structure in which the surface is cross-linked. In this case, the heat resistance of the water-absorbent resin composition is particularly high, and the water-stopping property is also easily improved. The water-absorbent resin particles having a structure in which the surface is cross-linked can be formed by treating the water-absorbent resin particles with a post-crosslinking agent described later (that is, the water-absorbent resin particles are preferably produced by a post-crosslinking step described later). In addition, the water-absorbent resin particles may also have a structure in which the inside is cross-linked using an internal cross-linking agent described later.
[0033] The water-absorbent resin particles described above may be formed of, for example, a polymer (particularly a crosslinked product) of a water-soluble ethylenically unsaturated monomer. In this case, when the water-absorbent resin composition is used as a water-stopping material, it can not only impart excellent water-stopping performance but also easily improve heat resistance.
[0034] As water-soluble ethylenically unsaturated monomers, for example, well-known monomers that are generally used for water-absorbent resins can be widely used. As water-soluble ethylenically unsaturated monomers, for example, (meth)acrylic acid (in this specification, "acrylic ..." and "methacrylic ..." are collectively referred to as "(meth)acrylic ...". The same applies hereinafter) and its salts; 2-(meth)acrylamide-2-methylpropanesulfonic acid and its salts; nonionic monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylate, N-hydroxymethyl(meth)acrylamide, and polyethylene glycol mono(meth)acrylate; unsaturated monomers containing amino groups such as N,N-diethylaminoethyl(meth)acrylate, N,N-diethylaminopropyl(meth)acrylate, and diethylaminopropyl(meth)acrylamide, and their quaternary products. These water-soluble ethylenically unsaturated monomers can be used alone or in combination (copolymerization) of two or more. Among them, (meth)acrylic acid and its salts are preferred, and (meth)acrylamide, N,N-dimethylacrylamide, (meth)acrylic acid and its salts are more preferred, from the viewpoint of more easily exhibiting the effects of the present invention.
[0035] When acrylic acid and salts thereof are used as these water-soluble ethylenically unsaturated monomers, acrylic acid and salts thereof are used as the main water-soluble ethylenically unsaturated monomers, preferably in an amount of 70 to 100 mol % based on the total molar number of the water-soluble ethylenically unsaturated monomers.
[0036] It should be noted that, in the reverse phase suspension polymerization described later, in order to improve the dispersion efficiency in the hydrocarbon dispersion medium, the water-soluble ethylenically unsaturated monomer can be used as an aqueous solution. The concentration of the monomer in the aqueous solution is not particularly limited, and is usually set to be 20% by mass or more and below the saturation concentration, preferably 25 to 90% by mass, and more preferably 30 to 85% by mass.
[0037] In the case where the water-soluble ethylenically unsaturated monomer has an acid group such as (meth) acrylic acid, 2-(meth) acrylamide-2-methylpropanesulfonic acid, etc., a water-soluble ethylenically unsaturated monomer in which the acid group is pre-neutralized with an alkaline neutralizer can be used as needed. Such alkaline neutralizers are not particularly limited, and examples thereof include alkali metal salts such as sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, and ammonia. In particular, in order to simplify the neutralization operation, these alkaline neutralizers can be used in the form of aqueous solutions. The above alkaline neutralizers can be used alone or in combination of two or more.
[0038] There is no particular limitation on the degree of neutralization of the water-soluble ethylenically unsaturated monomer by the alkaline neutralizer. In order to improve the water absorption performance by increasing the osmotic pressure of the obtained water-absorbent resin particles and to prevent problems in safety and the like due to the presence of the remaining alkaline neutralizer, the degree of neutralization of all acid groups of the water-soluble ethylenically unsaturated monomer is preferably set to 10 to 100 mol %, more preferably 30 to 80 mol %.
[0039] The water-absorbent resin particles can be produced, for example, by a production method including a step of performing a polymerization reaction using a raw material containing the above-mentioned water-soluble ethylenically unsaturated monomer (hereinafter referred to as a "polymerization step").
[0040] As the polymerization reaction carried out in the polymerization step, for example, reverse suspension polymerization, aqueous solution polymerization, emulsion polymerization, etc. can be cited. From the viewpoint of easily adjusting the 30-second swelling height of the water-absorbent resin composition to a predetermined range, it is preferred to adopt reverse suspension polymerization in the polymerization step. Reverse suspension polymerization refers to a method in which a poorly soluble monomer is suspended in a dispersion medium in the presence of a dispersion stabilizer and polymerized. As is well known, reverse suspension polymerization can be a multi-step polymerization in which the monomer is polymerized in multiple steps, for example, a two-step polymerization. In the multi-step polymerization, the initial polymerization reaction is referred to as the first step, and thereafter, the monomers added stepwise after the first step polymerization are referred to as the second step, the third step, etc. in sequence.
[0041] As the dispersion medium used in the reverse suspension polymerization, a hydrocarbon dispersion medium can be used. As the hydrocarbon dispersion medium, there can be listed: aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, and light petroleum (ligroin); alicyclic hydrocarbons such as cyclopentane, methylcyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbons such as benzene, toluene, and xylene. Among these dispersion media, n-hexane, n-heptane, and cyclohexane can be preferably used because they are easily available in industry, have stable quality, and are cheap. These dispersion media can be used alone or in combination of two or more. As the dispersion medium, for example, Exxsol Heptane (manufactured by ExxonMobil: hydrocarbons of heptane and its isomers), Nappar6 (manufactured by ExxonMobil: hydrocarbons of cyclohexane and its isomers), which are known as mixed solvents, can be used.
[0042] The water-soluble ethylenically unsaturated monomer that can be used in the reverse phase suspension polymerization is the same as the above-mentioned water-soluble ethylenically unsaturated monomer, and is preferably (meth)acrylic acid and its salts, (meth)acrylamide, and N,N-dimethylacrylamide from the viewpoint of excellent reactivity, and is more preferably (meth)acrylic acid and its salts. In addition, the water-soluble ethylenically unsaturated monomer may be subjected to a neutralization treatment so that the degree of neutralization is within the above-mentioned range.
[0043] In the polymerization reaction in the polymerization step, in particular, in the reversed phase suspension polymerization, a thickener may be used as needed. As the thickener, for example, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, carboxymethyl cellulose, polyacrylic acid, polyacrylic acid (partially) neutralized product, polyethylene glycol, polyacrylamide, polyethylene imine, dextrin, sodium alginate, polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene oxide, etc. can be used.
[0044] As the dispersion stabilizer used in the reversed suspension polymerization, a surfactant can be used, for example, sucrose fatty acid ester, polyglycerol fatty acid ester, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene glycerol fatty acid ester, sorbitol fatty acid ester, polyoxyethylene sorbitol fatty acid ester, polyoxyethylene alkyl ether, polyoxyethylene alkylphenyl ether, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, alkyl allyl formaldehyde condensation polyoxyethylene ether, polyoxyethylene polyoxypropylene block copolymer, polyoxyethylene polyoxypropyl alkyl ether, polyethylene glycol fatty acid ester, alkyl glucosides, N-alkyl glucamide, polyoxyethylene fatty acid amide, polyoxyethylene alkylamine, phosphate ester of polyoxyethylene alkyl ether, phosphate ester of polyoxyethylene alkyl allyl ether, etc. Among them, from the perspective of the dispersion stability of the monomer, sorbitan fatty acid ester, polyglycerol fatty acid ester, sucrose fatty acid ester, etc. are preferred. These surfactants can be used alone or in combination of two or more.
[0045] Regarding the amount of surfactant used, in order to maintain a good dispersion state of the water-soluble ethylenically unsaturated monomer in the hydrocarbon dispersion medium and obtain a dispersion effect commensurate with the amount used, it is preferably 0.1 to 30 parts by mass, more preferably 0.3 to 20 parts by mass, relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer in the first step.
[0046] In addition, as a dispersion stabilizer, a polymeric dispersant can be used in combination with a surfactant or in place of a surfactant. As usable polymeric dispersants, maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified EPDM (ethylene-propylene-diene terpolymer), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, ethyl cellulose, ethyl hydroxyethyl cellulose, etc. can be cited. Among them, maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, etc. are preferred from the perspective of the dispersion stability of the monomer. These polymeric dispersants may be used alone or in combination of two or more.
[0047] The amount of the polymer dispersant used is preferably 0.1 to 30 parts by mass, more preferably 0.3 to 20 parts by mass, relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer in the first step, in order to maintain a good dispersion state of the water-soluble ethylenically unsaturated monomer in the hydrocarbon dispersion medium and obtain a dispersing effect commensurate with the amount used.
[0048] In the polymerization step, for example, a widely known polymerization initiator can be used. Examples of free radical polymerization initiators include persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate; peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, di-tert-butyl peroxide, tert-butyl cumyl peroxide, and hydrogen peroxide; and azo compounds such as 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[2-(N-phenylamidino)propane] dihydrochloride, 2,2'-azobis[2-(N-allylamidino)propane] dihydrochloride, and 4,4'-azobis(4-cyanovaleric acid). Free radical polymerization initiators can also be used in combination with reducing agents such as sodium sulfite, sodium bisulfite, ferrous sulfate, and L-ascorbic acid to prepare redox polymerization initiators.
[0049] The lower limit of the amount of the free radical polymerization initiator used in the polymerization step is preferably 0.01 mmol, more preferably 0.05 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer used, from the viewpoint of polymerization stability. In addition, the upper limit of the free radical polymerization initiator is preferably 20 mmol, more preferably 10 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer used, from the viewpoint of polymerization stability. By using the free radical polymerization initiator within this range, the production of the water-absorbent resin becomes easy.
[0050] In the polymerization step, a chain transfer agent may be used as necessary. Examples of the chain transfer agent include hypophosphites, mercaptans, thiol acids, secondary alcohols, and amines.
[0051] In the polymerization process, an internal crosslinking agent may be used as needed. Thus, the polymer obtained in the polymerization process can have a structure obtained by crosslinking the inside of the polymer using the internal crosslinking agent. Therefore, in the case where the water-absorbent resin particles have a crosslinked structure inside the polymer, the internal crosslinked structure is formed when the water-soluble ethylenically unsaturated monomer is polymerized. In this specification, in order to distinguish it from the post-crosslinking agent described later, the crosslinking agent used in the internal crosslinking of the polymer is referred to as an internal crosslinking agent.
[0052] As the internal crosslinking agent, a compound having two or more polymerizable unsaturated groups can be cited. As a specific example of the internal crosslinking agent, (poly)ethylene glycol can be cited [in this specification, for example, "polyethylene glycol" and "ethylene glycol" are collectively referred to as "(poly)ethylene glycol". The same applies to the following], di- or tri-(meth)acrylates of polyols such as (poly)propylene glycol, trimethylolpropane, glycerol polyoxyethylene glycol, polyoxypropylene glycol and (poly)glycerol; unsaturated polyesters obtained by reacting the above polyols with unsaturated acids such as maleic acid and fumaric acid; bisacrylamides such as N,N'-methylenebis(meth)acrylamide; di- or tri-(meth)acrylates obtained by reacting polyepoxide with (meth)acrylic acid; di(meth)acrylic acid carbamates obtained by reacting polyisocyanates such as toluene diisocyanate and hexamethylene diisocyanate with hydroxyethyl (meth)acrylate; allylated starch; allylated cellulose; diallyl phthalate; N,N',N"-triallyl isocyanurate; divinylbenzene, etc.
[0053] As internal crosslinking agents, in addition to the above-mentioned compounds having two or more polymerizable unsaturated groups, compounds containing glycidyl groups such as (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerol diglycidyl ether can also be listed; (poly)ethylene glycol, (poly)propylene glycol, (poly)glycerol, pentaerythritol, ethylenediamine, polyethyleneimine, (meth)glycidyl acrylate, etc. It is also possible to use two or more of these internal crosslinking agents in combination. Among them, from the viewpoint of excellent reactivity at low temperatures, (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, (poly)glycerol diglycidyl ether and N,N'-methylenebisacrylamide are preferred.
[0054] When an internal crosslinking agent is used, the lower limit of the amount of the internal crosslinking agent used is preferably 0.0001 mmol, more preferably 0.0005 mmol, further preferably 0.001 mmol, and particularly preferably 0.01 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer used, from the perspective of ease of production of the water-absorbent resin. In addition, the upper limit of the amount of the internal crosslinking agent used is preferably 5 mmol, more preferably 0.5 mmol, further preferably 0.1 mmol, and particularly preferably 0.05 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer used. One or more types of internal crosslinking agents may be used.
[0055] In the polymerization step, the polymerization reaction temperature can be appropriately set according to the type and amount of the radical polymerization initiator, and can be set to, for example, 20 to 110° C., preferably 40 to 90° C. The reaction time can be set to, for example, 0.1 hour to 4 hours.
[0056] In the polymerization step, for example, the polymerization can be carried out in the following manner: an aqueous solution containing a water-soluble ethylenically unsaturated monomer, a thickener, a free radical polymerization initiator and an internal crosslinking agent, which has been neutralized as required, is added to a dispersion medium in which a polymer dispersion stabilizer is dissolved, and then a surfactant is added to form a suspension state. It should be noted that the order of adding the raw materials is not limited to this.
[0057] Through the above-mentioned polymerization process, the water-soluble ethylenically unsaturated monomer is polymerized to generate a polymer. For example, a slurry of a polymer in which a water-soluble ethylenically unsaturated monomer is dispersed is obtained in reverse suspension polymerization. When an internal crosslinking agent is used, the polymer obtained in the polymerization process has a structure obtained by crosslinking using the internal crosslinking agent.
[0058] In the polymerization step, in the case of the above-mentioned multi-step polymerization, the first step of reversed phase suspension polymerization can be carried out by the above-mentioned method, and then a water-soluble ethylenically unsaturated monomer is added to the reaction mixture obtained in the first step of the polymerization step and mixed, and the reversed phase suspension polymerization of the second and subsequent steps can be carried out by the same method as the first step. In the reversed phase suspension polymerization of each step after the second step, in addition to the water-soluble ethylenically unsaturated monomer, a free radical polymerization initiator and an internal crosslinking agent added as needed can be added within the range of the molar ratio of each component to the water-soluble ethylenically unsaturated monomer based on the amount of the water-soluble ethylenically unsaturated monomer added in the reversed phase suspension polymerization of each step after the second step, and the reversed phase suspension polymerization can be carried out under the same conditions as the above-mentioned method.
[0059] When reversed phase suspension polymerization is performed in multiple steps, it is preferred that the total amount of the polymerization initiator and the amount of the internal crosslinking agent used as required be within the above ranges relative to 1 mol of the water-soluble ethylenically unsaturated monomer used in the reversed phase suspension polymerization from the viewpoint of easily producing the desired water-absorbent resin.
[0060] The method for producing water-absorbent resin particles may include a drying step for drying the polymer obtained by the polymerization step. The drying step is a step for removing water from the polymer obtained in the above-mentioned polymerization step or the polymer obtained by crosslinking with an internal crosslinking agent by applying energy such as heat to the polymer from the outside. For example, in the case of reverse suspension polymerization, in the drying step, water, hydrocarbon dispersion medium, etc. can be removed from the polymer by performing azeotropic distillation in a state where the polymer (water-containing gel) obtained in the above-mentioned polymerization step is dispersed in a hydrocarbon dispersion medium. By implementing the drying step, the water content of the polymer or the polymer obtained by crosslinking with an internal crosslinking agent can be adjusted. It should be noted that the drying step can be implemented simultaneously with the post-crosslinking step described later.
[0061] The drying process may be carried out under normal pressure or under reduced pressure. In order to improve the drying efficiency, it may be carried out under a stream of nitrogen or the like. When the drying process is carried out under normal pressure, the drying temperature is preferably 70 to 250° C., more preferably 80 to 180° C., further preferably 80 to 140° C., and particularly preferably 90 to 130° C. When the drying process is carried out under reduced pressure, the drying temperature is preferably 40 to 160° C., more preferably 50 to 120° C.
[0062] The polymer obtained in the above-mentioned polymerization step (including the polymer obtained by crosslinking with an internal crosslinking agent) or the polymer obtained in the above-mentioned drying step (including the polymer obtained by crosslinking with an internal crosslinking agent) can be treated with a post-crosslinking agent. As a result, the polymer can have a structure obtained by crosslinking with a post-crosslinking agent, and the crosslinking density near the surface of the water-absorbent resin is increased. The method of treating the polymer with a post-crosslinking agent can widely adopt a known method. The process of treating the polymer with a post-crosslinking agent is recorded as a "post-crosslinking process". The treatment with a post-crosslinking agent can be performed, for example, in the above-mentioned dispersion medium.
[0063] The types of post-crosslinking agents include, for example, those that can be used in conventional water-absorbent resins. The post-crosslinking agent can use a compound having two or more reactive functional groups. Specific examples of post-crosslinking agents include: polyols such as ethylene glycol, propylene glycol, 1,4-butanediol, trimethylolpropane, glycerol, polyoxyethylene glycol, polyoxypropylene glycol, and polyglycerol; polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)glycerol diglycidyl ether, (poly)glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and (poly)glycerol polyglycidyl ether; epichlorohydrin, epoxy Halogenated epoxy compounds such as bromopropane and α-methyl epichlorohydrin; isocyanate compounds such as 2,4-toluene diisocyanate and hexamethylene diisocyanate; oxetane compounds such as 3-methyl-3-oxetane methanol, 3-ethyl-3-oxetane methanol, 3-butyl-3-oxetane methanol, 3-methyl-3-oxetane ethanol, 3-ethyl-3-oxetane ethanol, 3-butyl-3-oxetane ethanol; 1,2-ethylenedioxy Oxazoline, etc. Oxazoline compounds; carbonate compounds such as ethylene carbonate; hydroxyalkylamide compounds such as bis[N,N-di(β-hydroxyethyl)]adipamide, etc. Among them, more preferred are polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)ethylene glycol triglycidyl ether, (poly)glycerol diglycidyl ether, (poly)glycerol triglycidyl ether, (poly)propylene glycol polyglycidyl ether, (poly)glycerol polyglycidyl ether, etc. The post-crosslinking agent may be used alone or in combination of two or more.
[0064] The lower limit of the amount of the post-crosslinking agent used is preferably 0.01 millimole, more preferably 0.05 millimole, and further preferably 0.1 millimole relative to 1 mole of the water-soluble ethylenically unsaturated monomer constituting the post-crosslinked polymer, from the viewpoint of easily adjusting the 30-second swelling height to a specified range. In addition, the upper limit is preferably 10 millimoles, more preferably 5 millimoles, and further preferably 2 millimoles relative to 1 mole of the water-soluble ethylenically unsaturated monomer.
[0065] The reaction temperature in the post-crosslinking step (i.e., the temperature at which the polymer is treated with the post-crosslinking agent) is preferably 50 to 250° C., more preferably 60 to 180° C., and even more preferably 60 to 140° C. The reaction time for the post-crosslinking (i.e., the time for treating the polymer with the post-crosslinking agent at the reaction temperature) varies depending on the reaction temperature, the type and amount of the post-crosslinking agent used, and therefore cannot be generalized, but is generally 1 to 300 minutes, preferably 5 to 200 minutes.
[0066] In the present invention, there may be a step of adding a phosphonic acid chelating agent described later before, during or after the post-crosslinking step. Hereinafter, this step is referred to as a "chelating agent adding step". By the chelating agent adding step, a phosphonic acid chelating agent is added during the production process of the water-absorbent resin particles, and thus the obtained water-absorbent resin particles may contain a phosphonic acid chelating agent. For example, a phosphonic acid chelating agent may be arranged near the surface of the water-absorbent resin particles.
[0067] In the chelating agent adding step, for example, the phosphonic acid chelating agent can be mixed with the polymer before post-crosslinking (i.e., before adding the post-crosslinking agent), or the chelating agent can be mixed with the polymer after post-crosslinking (i.e., after adding the post-crosslinking agent), or a combination of these can be used. That is, in the method for producing water-absorbent resin particles, the polymer can be post-crosslinked after the phosphonic acid chelating agent is mixed with the polymer before post-crosslinking, or the phosphonic acid chelating agent can be mixed with the polymer after post-crosslinking. In addition, in the method for producing water-absorbent resin particles, the following steps can also be performed: the phosphonic acid chelating agent is mixed with the polymer before post-crosslinking, and then the polymer is post-crosslinked, and then the phosphonic acid chelating agent is mixed with the polymer after post-crosslinking.
[0068] The amount of the phosphonic acid chelating agent used can be appropriately adjusted to 0.01 to 40 μmol per 1 g of the obtained water-absorbent resin particles.
[0069] It should be noted that the phosphonic acid chelating agent does not necessarily need to be added when the water-absorbent resin particles are produced, and the water-absorbent resin particles produced in advance may be mixed with the phosphonic acid chelating agent as described later.
[0070] In the method for producing water-absorbent resin particles, additives may be added according to the purpose in order to impart various properties to the obtained water-absorbent resin particles after the polymerization step. Examples of such additives include various additives that have been conventionally added to water-absorbent resins, such as inorganic powders, surfactants, oxidants, reducing agents, free radical chain inhibitors, antioxidants, antibacterial agents, deodorants, and the like.
[0071] The water content of the water-absorbent resin particles may be, for example, 20.0 mass % or less, 15.0 mass % or less, or 10.0 mass % or less based on the total mass of the water-absorbent resin particles. The water content based on the total mass of the water-absorbent resin particles is measured by the method described in "Measurement of Water Content" below.
[0072] (Phosphonic acid chelating agent)
[0073] Regarding the type of phosphonic acid chelating agent contained in the water-absorbent resin composition of the present invention, for example, a wide range of known phosphonic acid chelating agents can be used. A phosphonic acid chelating agent refers to a compound having at least two phosphonic acid sites in a molecule. The phosphonic acid chelating agent may be in the form of a salt, that is, the phosphonic acid site may form a salt.
[0074] Examples of the phosphonic acid chelating agent include ethylenediaminetetramethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, nitrotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, 1-diphosphonic acid, diethylenetriaminepenta(methylenephosphonic acid), and salts thereof.
[0075] When the phosphonic acid chelating agent is in the form of a salt, examples of the salt include: alkali metal salts such as sodium and potassium; alkaline earth metal salts such as magnesium and calcium; organic amine salts, ammonium salts, etc. For the phosphonic acid chelating agent, all or part of the ligand may form a salt. When the phosphonic acid chelating agent is in the form of a salt, examples include: ethylenediaminetetramethylenephosphonic acid pentasodium salt, diethylenetriaminepentamethylenephosphonic acid heptasodium salt.
[0076] The chelating agent contained in the water-absorbent resin composition of the present invention may be used alone or in combination of two or more. The number of ligands in the chelating agent may be, for example, 2, 3 or 4 at the lower limit and 12, 11 or 10 at the upper limit.
[0077] (Water-absorbent resin composition)
[0078] As described above, the water-absorbent resin composition of the present invention contains 0.01 to 40 μmol (0.01 μmol or more and 40 μmol or less) of the phosphonic acid chelating agent relative to 1 g of the water-absorbent resin particles. When the content of the phosphonic acid chelating agent is less than 0.01 μmol or more than 40 μmol relative to 1 g of the water-absorbent resin particles, the heat resistance of the water-absorbent resin composition decreases, and it is difficult to use it as a water-stopping material. That is, in the present invention, the heat resistance of the water-absorbent resin composition is improved only when the content ratio of the phosphonic acid chelating agent is within a specific range.
[0079] The water-absorbent resin particles as a basis for the content of the phosphonic acid chelating agent may be composed of a polymer of a water-soluble ethylenically unsaturated monomer, an initiator, a crosslinking agent, and the water contained in the water-absorbent resin particles. In addition, the water-absorbent resin particles may contain a thickener, a surfactant, and a polymer dispersant used in the polymerization process. In addition, the water-absorbent resin particles may contain various additives added after the polymerization process. Examples of additives include inorganic powders, surfactants, oxidants, reducing agents, free radical chain inhibitors, antioxidants, antibacterial agents, deodorants, and the like.
[0080] The content of the phosphonic acid chelating agent is preferably 0.1 μmol or more, more preferably 0.5 μmol or more, and further preferably 1.5 μmol or more, based on 1 g of the water-absorbent resin particles. The content of the phosphonic acid chelating agent is preferably 30 μmol or less, more preferably 25 μmol or less, further preferably 18 μmol or less, further preferably 13 μmol or less, and particularly preferably 10 μmol or less, based on 1 g of the water-absorbent resin particles.
[0081] From the viewpoint of improving the heat resistance of the water-absorbent resin composition, the content of phosphonic acid in the phosphonic acid chelating agent is preferably 0.4 μmol or more, more preferably 2.0 μmol or more, and even more preferably 6.0 μmol or more, based on 1 g of the water-absorbent resin particles. The content of phosphonic acid in the phosphonic acid chelating agent is preferably 150 μmol or less, more preferably 100 μmol or less, even more preferably 80 μmol or less, even more preferably 65 μmol or less, and particularly preferably 50 μmol or less, based on 1 g of the water-absorbent resin particles.
[0082] The method for preparing the water-absorbent resin composition of the present invention can be, for example, by mixing water-absorbent resin particles and a phosphonic acid chelating agent at a predetermined ratio to obtain the water-absorbent resin composition of the present invention. In this case, the phosphonic acid chelating agent can be mixed with the water-absorbent resin particles in a solid state such as powder (so-called dry mixing method) or in a solution state dissolved in a solvent such as water.
[0083] In addition, as another method for preparing the water-absorbent resin composition of the present invention, there can be cited a method using the water-absorbent resin particles obtained through the above-mentioned chelating agent adding step. That is, the water-absorbent resin particles obtained through the chelating agent adding step contain water-absorbent resin particles and a phosphonic acid-based chelating agent, and therefore, by using the water-absorbent resin particles obtained through the chelating agent adding step, the water-absorbent resin composition of the present invention can be prepared. For example, the water-absorbent resin particles obtained through the chelating agent adding step can be used as the water-absorbent resin composition of the present invention.
[0084] The water-absorbent resin composition of the present invention may contain other components besides the water-absorbent resin particles and the phosphonic acid chelating agent. Examples of other components include silicon dioxide. When the water-absorbent resin composition of the present invention contains silicon dioxide, the content ratio thereof is, for example, 0.01 to 5 parts by mass, preferably 0.02 to 3 parts by mass, and more preferably 0.05 to 1 part by mass relative to 100 parts by mass of the water-absorbent resin particles. The water-absorbent resin composition of the present invention may contain other components besides silicon dioxide, for example, various components contained in known water-stopping materials.
[0085] The water-absorbent resin composition of the present invention preferably contains 50% by mass or more of water-absorbent resin particles and a phosphonic acid chelating agent, more preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more. The water-absorbent resin composition of the present invention may consist only of water-absorbent resin particles and a phosphonic acid chelating agent, or may consist only of water-absorbent resin particles, a phosphonic acid chelating agent, and silica.
[0086] The median particle size of the water-absorbent resin composition of the present invention is, for example, 10 to 500 μm, preferably 30 to 300 μm, more preferably 50 to 250 μm, and even more preferably 100 to 200 μm from the viewpoint that the 30-second swelling height described later is easily within a desired range. The water-absorbent resin of the present invention may be in various shapes, for example, spherical, crushed, granular, ellipsoidal, scaly, rod-like, blocky, and the like.
[0087] As described above, the 30-second swelling height of the water-absorbent resin composition of the present invention is preferably 6.0 mm or more. In this case, the water-absorbent resin composition of the present invention can make the water-stop material have excellent swelling performance and can improve the water-stopping property. In the case where the water-absorbent resin particles contained in the water-absorbent resin composition of the present invention have a structure in which the surface is cross-linked, the 30-second swelling height can easily reach 6.0 mm or more. It should be noted that the 30-second swelling height of the water-absorbent resin composition of the present invention can be measured according to the measurement method described in "Measurement of 30-second swelling height".
[0088] The 30-second swelling height of the water-absorbent resin composition of the present invention is more preferably 8.0 mm or more, further preferably 10.0 mm or more, and particularly preferably 12.0 mm or more. In addition, the upper limit of the 30-second swelling height may be 26.0 mm or 18.0 mm. The 30-second swelling height of the water-absorbent resin composition can be adjusted by appropriately selecting the type of water-absorbent resin particles, the median particle size, and the type of chelating agent.
[0089] The value of the gel viscosity retention rate S of the water-absorbent resin composition of the present invention after being kept at 90°C for 4 days is preferably 20% or more. In this case, it can be said that the water-absorbent resin composition has better heat resistance. The value of the gel viscosity retention rate S of the water-absorbent resin composition of the present invention after being kept at 90°C for 4 days is more preferably 40% or more, and further preferably 60% or more. It should be noted that the gel viscosity retention rate S of the water-absorbent resin composition of the present invention after being kept at 90°C for 4 days can be calculated according to the measurement method described in "Measurement of gel viscosity retention rate".
[0090] The value of the gel viscosity of the water-absorbent resin composition of the present invention after being kept at 90°C for 4 days is preferably 5000 mPa·s or more. In this case, it can be said that the water-absorbent resin composition has better heat resistance. The value of the gel viscosity of the water-absorbent resin composition of the present invention after being kept at 90°C for 4 days is more preferably 10000 mPa·s or more, further preferably 15000 mPa·s or more, and particularly preferably 20000 mPa·s or more. In addition, the value of the gel viscosity after being kept at 90°C for 4 days may be 80000 mPa·s or less, or 60000 mPa·s or less.
[0091] The water-absorbent resin composition of the present invention has excellent heat resistance and is therefore suitable for various applications, such as industrial materials such as waterproof materials and anti-condensation agents, agricultural and horticultural materials such as water-retaining agents and soil improvers, and sanitary materials such as diapers and sanitary products. In particular, the water-absorbent resin of the present invention can maintain a waterproof effect for a long time and is therefore suitable for use in waterproof materials.
[0092] [Evaluation of water-absorbent resin particles]
[0093] Unless otherwise specified, the measurements were performed under an environment of a temperature of 25±2° C. and a humidity of 50±10%.
[0094] (Determination of moisture content)
[0095] Place 2.0 g of water-absorbent resin particles in an aluminum foil box that is pre-set to a constant weight (W1 (g)), gently close the mouth of the aluminum foil box, and accurately weigh the total mass W2 (g) of the aluminum foil box containing the sample. Use a hot air dryer set at an internal temperature of 200°C to dry the aluminum foil box containing the sample for 2 hours. Cool the dried aluminum foil box containing the sample in a dryer to room temperature. Measure the total mass W3 (g) of the aluminum foil box containing the sample after cooling. Calculate the moisture content of the sample by the following formula.
[0096] Moisture content [mass %] = {(W2-W3) / (W2-W1)} × 100
[0097] [Evaluation of water-absorbent resin composition]
[0098] Unless otherwise specified, the measurements were performed under an environment of a temperature of 25±2° C. and a humidity of 50±10%.
[0099] (Measurement of median particle size (particle size distribution))
[0100] 5 g of the water-absorbent resin composition was sieved using a sonic vibration sieve measuring device (Robot Shifter), sieves with mesh sizes of 850 μm, 500 μm, 250 μm, 180 μm, 150 μm, 106 μm and 75 μm according to the JIS standard, and a tray. The mass of the particles remaining on each sieve was calculated as a mass percentage relative to the total amount. The mass percentage of the particles remaining on each sieve was accumulated in order from the particles with the largest particle size, and the relationship between the mesh size of the sieve and the cumulative value of the mass percentage of the particles remaining on the sieve was plotted on a logarithmic probability paper. The particle size corresponding to the cumulative mass percentage of 50% was obtained by connecting the scattered points on the probability paper with a straight line, and it was taken as the median particle size of the water-absorbent resin composition.
[0101] (30-second swelling height measurement)
[0102] use Figure 1 The swelling height measuring device X shown measures the swelling height of the water-absorbent resin composition. Figure 1 The swelling height measuring device X shown in the figure comprises a moving distance measuring device 1, a concave circular cup 2 (45 mm in height, 90 mm in outer diameter, 40 mm in depth of the concave portion, 80 mm in inner diameter of the concave portion), a plastic convex circular cylinder 3 (79 mm in outer diameter, 60 through holes 7 with a diameter of 2 mm evenly arranged on the contact surface with the water-absorbent resin composition), and a nonwoven fabric 4 (weight per unit area 11 g / m 2 The swelling height measuring device X can measure the displacement of the distance moved by the convex circular cylinder 3 in units of 0.01 mm using the laser 6. The concave circular cup 2 can evenly spread a predetermined amount of the water-absorbent resin composition. The convex circular cylinder 3 can evenly apply a load of 90 g to the water-absorbent resin composition 5 as a sample.
[0103] First, 0.2 g of the sample (water-absorbent resin composition 5) is uniformly spread in the concave circular cup 2, and a nonwoven fabric 4 is laid on it. Then, the convex circular cylinder 3 is gently placed on the nonwoven fabric 4, and the laser 6 of the sensor of the moving distance measuring device 1 is set to reach the center of the cylinder 3. Ion exchange water adjusted to 20° C. in advance is poured into the concave circular cup 2 through the through hole 7 of the convex circular cylinder 3 to swell the water-absorbent resin composition 5. The time when the laser senses that the water-absorbent resin composition 5 is swollen and the convex circular cylinder 3 is pushed up is regarded as the start of water absorption (0 seconds) (automatic measurement starts when a displacement of 0.5 mm occurs), and the distance (the displacement difference of the convex circular cylinder 3 in the direction perpendicular to the bottom surface of the concave part of the concave circular cup 2) by which the water-absorbent resin composition 5 is swollen and the convex circular cylinder 3 is pushed up is measured. The water level of the ion exchanged water was checked every 3 seconds from the start of the injection of the ion exchanged water, and the ion exchanged water was continuously injected intermittently so that the water surface was maintained at a height near the flat surface of the flat plate portion of the convex circular cylindrical body 3. 30 seconds after the moment when the water-absorbent resin composition 5 started to absorb water (more precisely, the moment when the water-absorbent resin composition absorbed a very small amount of ion exchanged water and the cylindrical body 3 was pushed up by 0.5 mm), the distance by which the convex circular cylindrical body 3 was pushed up (including the height (0.5 mm) by which the cylindrical body 3 was pushed up at the moment when the water absorption started) was recorded as the 30-second swelling height.
[0104] (Measurement of gel viscosity retention; evaluation of heat resistance)
[0105] The gel viscosity of the water-absorbent resin composition was measured by adjusting the temperature of the swollen gel to 25±0.5° C. using a Brookfield type rotational viscometer (type A, spindle rotor No. 5, rotation speed 10 rpm). The gel viscosity was measured in a state where the gel was placed in a 200 mL glass beaker with an inner diameter of 64 mmφ to a height of 65 mm.
[0106] 100 g of ion exchange water was added to a 200 mL beaker, and stirred at 600 rpm using a magnetic stirring bar (cylindrical shape with a diameter of 8 mm × a length of 30 mm, without a ring). 2.0 g of the water-absorbent resin composition was added to the vortex generated by the stirring, and then stirred until the magnetic stirrer stopped due to the generated gel. This operation was performed twice in total, thereby obtaining a swollen gel equivalent to 4.0 g of the water-absorbent resin composition before swelling. 200 g of the swollen gel thus obtained was placed in a 250 mL glass heat-resistant bottle, and allowed to stand in a hot air dryer at 90±2°C. The viscosity of the swollen gel after 2 days and 4 days was measured, and the gel viscosity retention rate S was calculated by the following formula (I), and this value was used as an indicator of heat resistance.
[0107] Gel viscosity retention rate S = B / A (I)
[0108] (In formula (I), A represents the gel viscosity after 2 days (mPa·s), and B represents the gel viscosity after 4 days (mPa·s))
[0109] 2. Water-stop materials and cables
[0110] As long as the water-absorbing resin composition of the present invention is provided, the water-absorbing resin composition of the present invention may be configured in the same manner as a known water-absorbing resin composition. The water-absorbing resin composition may be formed by the water-absorbing resin composition alone. Alternatively, the water-absorbing resin composition may be formed by molding a mixture with rubber and / or a thermoplastic resin. Examples of the water-absorbing resin composition include water-absorbing tapes, water-absorbing yarns, and the like.
[0111] The water stop can be obtained, for example, by holding the water-absorbent resin composition on a liquid-permeable sheet. Alternatively, the water stop can be obtained by sandwiching the water-absorbent resin composition between two or more liquid-permeable sheets. Specifically, the water stop can be obtained by using an adhesive to adhere the water-absorbent resin composition to a liquid-impermeable sheet to form a sheet. As the liquid-permeable sheet, for example, non-woven fabrics, woven fabrics, films, etc. made of synthetic resins such as polyolefins, polyesters, polyamides, nylons, and acrylics can be used.
[0112] The water-stop yarn can be obtained, for example, by coating the water-absorbent resin composition of the present invention on a substrate or impregnating the substrate. The substrate may be a long fiber or plastic yarn (substrate yarn) of a synthetic fiber, specifically, a long fiber or plastic yarn of a synthetic resin such as polyolefin, polyester, polyamide, nylon, or acrylic.
[0113] In the production of the water-stop yarn, the method of coating the water-absorbent resin composition on the substrate or impregnating the substrate is not particularly limited. For example, the water-absorbent resin composition may be adhered to the substrate by coating a dispersion obtained by dispersing the water-absorbent resin composition in an organic solvent on the substrate or impregnating the substrate. In the case where the water-absorbent resin composition has weak adhesion to the substrate, an adhesive may be used in combination to improve adhesion.
[0114] Examples of the adhesive include natural rubber, butyl rubber, polyisoprene and other rubber adhesives; styrene-based elastomer adhesives such as styrene-isoprene block copolymers (SIS) and styrene-butadiene block copolymers (SBS); ethylene-vinyl acetate copolymer (EVA) adhesives; ethylene-ethyl acrylate copolymers (EEA) and other ethylene-acrylic acid derivative copolymer adhesives; ethylene-acrylic acid copolymer (EAA) adhesives; polyamide adhesives such as copolymerized nylon; polyolefin adhesives such as polyethylene and polypropylene; polyester adhesives such as polyethylene terephthalate (PET) and copolymerized polyesters; and acrylic adhesives.
[0115] The waterproof material of the present invention contains the water-absorbing resin composition of the present invention and therefore has excellent heat resistance. In particular, even if the waterproof material absorbs water and gels and is left in a high temperature environment, the gel is unlikely to deteriorate and the waterproof performance is unlikely to decrease.
[0116] The water-stopping material of the present invention can be applied to various purposes, such as optical cables and other communication cables and various cables such as power cables, and is particularly suitable for use in power cables used underground and under the sea. In particular, the above-mentioned water-stopping tapes, water-stopping yarns, etc. are particularly suitable as water-stopping materials for power cables.
[0117] As a power cable, as long as it has the above-mentioned water-stopping material, its structure is not particularly limited. For example, the same structure as the known power cable can be adopted. Like a general power cable, it can have a structure in which an internal semiconductive layer, an insulating layer, an external semiconductive layer, and a coating layer are sequentially arranged on the outer periphery of the central conductor. In order to prevent water intruding from the outside from traveling along the length direction of the cable, a waterstop is arranged between the external semiconductive layer and the coating. In addition, the waterstop can be arranged between the internal semiconductive layer and the insulating layer. In addition, a waterstop yarn can also be accommodated in the central conductor.
[0118] When determining the inventions included in the present invention, each configuration (property, structure, function, etc.) described in each embodiment of the present invention can be arbitrarily combined. That is, the present invention includes all the themes consisting of all combinations of the configurations that can be combined as described in this specification.
[0119] Example
[0120] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples. It should be noted that the water-absorbent resin particles obtained in the following production examples and the water-absorbent resin compositions obtained in the examples and comparative examples were evaluated by various test methods described below. Unless otherwise specified, the measurements were performed under an environment of a temperature of 25±2°C and a humidity of 50±10%.
[0121] [Manufacturing of water-absorbent resin particles]
[0122] (Production Example 1)
[0123] A round-bottom cylindrical separable flask with an inner diameter of 11 cm and a capacity of 2 L was prepared, which was equipped with a reflux condenser, a dropping funnel, a nitrogen inlet tube, and a stirring blade having four inclined blades with a blade diameter of 5 cm in two stages as a stirrer. 292 g of n-heptane as a hydrocarbon dispersion medium was measured in the flask, 0.782 g of maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., HI-WAX1105A) as a polymer dispersant was added, and the temperature was raised to 80° C. while stirring to dissolve the dispersant, and then cooled to 56° C. On the other hand, 92.0 g (1.03 mol) of an 80.5% by mass acrylic acid aqueous solution as a water-soluble ethylenically unsaturated monomer was measured in a beaker with an internal volume of 300 mL, and 102.8 g of a 30% by mass sodium hydroxide aqueous solution was added dropwise while cooling with ice water to prepare a 75 mol % neutralized product of acrylic acid. 44.7 g of water, 0.0644 g (0.238 mmol) of potassium persulfate as a water-soluble radical polymerization agent, and 0.0102 g (0.059 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were further added and dissolved to prepare an aqueous liquid for the first step. The aqueous liquid was added to a separable flask and stirred for 10 minutes, and then a surfactant solution of 0.782 g of HLB3 sucrose stearate (Mitsubishi Chemical Foods Co., Ltd., Ryoto Sucrose Ester S-370) dissolved in 7.04 g of n-heptane as a surfactant was further added to a 20 mL-tube bottle, and the rotation speed of the stirrer was set to 450 rpm. While stirring, the system was fully replaced with nitrogen, and then the flask was immersed in a 70°C water bath to increase the temperature, and polymerization was carried out for 60 minutes, thereby obtaining a polymerization slurry for the first step.
[0124] On the other hand, 101.2 g (1.13 mol) of an 80.5% by mass acrylic acid aqueous solution as a water-soluble ethylenically unsaturated monomer was weighed in another beaker having an internal volume of 500 mL, and 113.1 g of a 30% by mass sodium hydroxide aqueous solution was added dropwise while cooling with ice water to prepare a 75 mol% neutralized product of acrylic acid. Further, 13.2 g of water, 0.081 g (0.300 mmol) of potassium persulfate as a water-soluble free radical polymerization agent, and 0.0092 g (0.053 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were added and dissolved to prepare an aqueous liquid for the second step.
[0125] The rotation speed of the stirrer was set to 1000 rpm, and the inside of the separable flask system was cooled to 31° C. while stirring, and then the entire amount of the aqueous liquid in the second step was added to the polymerization slurry in the first step, and the inside of the system was replaced with nitrogen for 30 minutes, and then the flask was immersed in a 70° C. water bath to raise the temperature, and a polymerization reaction was carried out for 60 minutes to obtain a slurry containing a hydrogel polymer 1. Then, the flask containing the slurry containing the hydrogel polymer 1 was immersed in an oil bath set to 125° C., and 243.2 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing n-heptane. Then, 7.15 g (0.821 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask, and the mixture was kept at 83° C. for 2 hours. Next, the n-heptane was heated in an oil bath at 125° C. to evaporate and dry, and then passed through a sieve with an opening of 850 μm to obtain 196.5 g of water-absorbent resin particles (1). The water content of the water-absorbent resin particles (1) was 4.6% by mass.
[0126] (Production Example 2)
[0127] A round-bottom cylindrical separable flask with an inner diameter of 11 cm and a capacity of 2 L was prepared, which was equipped with a reflux condenser, a dropping funnel, a nitrogen inlet pipe, and a stirring blade (coated with a fluororesin on the surface) having four inclined paddle blades with a blade diameter of 5 cm in two stages as a stirrer. 471 g of n-heptane as a hydrocarbon dispersion medium and 1.10 g of HLB8.6 sorbitan monolaurate (manufactured by NOF Corporation, trade name NONION LP-20R) as a surfactant were added to the flask, and the temperature was raised to 46° C. On the other hand, 92.0 g (1.03 mol) of an 80.5% by mass acrylic acid aqueous solution as a water-soluble ethylenically unsaturated monomer was measured in a beaker with an internal volume of 300 mL, and 102.8 g of a 30% by mass sodium hydroxide aqueous solution was added dropwise while cooling with ice water to prepare a 75 mol % neutralized product of acrylic acid. 44.6 g of water and 0.1012 g (0.374 mmol) of potassium persulfate as a water-soluble free radical polymerization agent were further added and dissolved to prepare an aqueous liquid. The aqueous liquid was added to a separable flask, the rotation speed of the stirrer was set to 700 rpm, and the inside of the flask was replaced with nitrogen for 30 minutes while stirring. Then, the flask was immersed in a 70°C water bath to increase the temperature, and polymerization was performed for 60 minutes to obtain a slurry containing a hydrogel polymer 2.
[0128] After the polymerization, 0.41 g (0.047 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether was added to the flask containing the slurry containing the hydrogel polymer 2. Next, the flask was immersed in an oil bath set at 125°C, and 103.3 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing the n-heptane. Then, 2.76 g (0.317 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask and kept at 83°C for 2 hours. Then, the n-heptane was heated in an oil bath at 125°C to evaporate and dry, and further passed through a sieve with a mesh size of 850 μm to obtain 68.0 g of water-absorbent resin particles (2). The water content of the water-absorbent resin particles (2) was 3.5% by mass.
[0129] [Production of water-absorbent resin composition]
[0130] (Example 1)
[0131] 0.1 parts by mass of amorphous silica (Tokusil NP-S, Oriental Silicas Corporation) was mixed with 100 parts by mass of the water-absorbent resin particles (1) obtained in Production Example 1. 0.001 parts by mass of ethylenediaminetetramethylenephosphonic acid (hereinafter referred to as EDTMP·8H) as a phosphonic acid chelating agent was added in a powder state to the mixture (0.023 μmol of EDTMP·8H per 1 g of the water-absorbent resin particles) and mixed thoroughly to obtain a water-absorbent resin composition (1). The median particle size of the water-absorbent resin composition (1) was 179 μm, and the 30-second swelling height was 8.3 mm.
[0132] (Example 2)
[0133] A water-absorbent resin composition (2) was obtained in the same manner as in Example 1 except that the amount of EDTMP·8H used was changed to 0.01 parts by mass (0.23 μmol of EDTMP·8H per 1 g of water-absorbent resin particles). The median particle size of the water-absorbent resin composition (2) was 179 μm, and the 30-second swelling height was 8.8 mm.
[0134] (Example 3)
[0135] A water-absorbent resin composition (3) was obtained in the same manner as in Example 1 except that the amount of EDTMP·8H used was changed to 0.1 parts by mass (2.3 μmol of EDTMP·8H per 1 g of water-absorbent resin particles). The median particle size of the water-absorbent resin composition (3) was 179 μm, and the 30-second swelling height was 7.9 mm.
[0136] (Example 4)
[0137] A water-absorbent resin composition (4) was obtained in the same manner as in Example 1 except that the amount of EDTMP·8H used was changed to 0.2 parts by mass (4.6 μmol of EDTMP·8H per 1 g of water-absorbent resin particles). The median particle size of the water-absorbent resin composition (4) was 179 μm, and the 30-second swelling height was 8.5 mm.
[0138] (Example 5)
[0139] A slurry containing the hydrogel polymer 1 was prepared by the same method as in Production Example 1. The flask containing the slurry containing the hydrogel polymer 1 was immersed in an oil bath set at 125° C., and 243.7 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing the n-heptane, and 0.72 g of a 32% by mass aqueous solution of ethylenediaminetetramethylenephosphonic acid pentasodium salt (hereinafter abbreviated as EDTMP·5Na) as a phosphonic acid chelating agent (2.1 μmol of EDTMP·5Na per 1 g of water-absorbent resin particles) was added. Then, 7.15 g (0.821 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask, and the mixture was kept at 83° C. for 2 hours. Next, the n-heptane was heated in an oil bath at 125° C. to evaporate and dry, thereby obtaining 198.4 g of water-absorbent resin particles. The mixture was then passed through a sieve with a mesh size of 850 μm to obtain 195.3 g of water-absorbent resin particles (3). The water content of the water-absorbent resin particles (3) was 3.6% by mass. 0.1 parts by mass of amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) was mixed with 100 parts by mass of the water-absorbent resin particles to obtain a water-absorbent resin composition (5). The median particle size of the water-absorbent resin composition (5) was 166 μm, and the 30-second swelling height was 8.3 mm.
[0140] (Example 6)
[0141] A slurry containing the hydrogel polymer 1 was prepared by the same method as in Production Example 1. The flask containing the slurry containing the hydrogel polymer 1 was immersed in an oil bath set at 125° C., and 243.9 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing the n-heptane, and 0.99 g of a 31% by mass aqueous solution of diethylenetriaminepentamethylenephosphonic acid heptasodium salt (hereinafter, abbreviated as DTPMP·7Na) as a phosphonic acid chelating agent (2.1 μmol of DTPMP·7Na per 1 g of water-absorbent resin particles) was added. Then, 7.15 g (0.821 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask, and the mixture was kept at 83° C. for 2 hours. Next, the n-heptane was heated in an oil bath at 125° C. to evaporate and dry, thereby obtaining 197.8 g of water-absorbent resin particles. The mixture was then passed through a sieve with a mesh size of 850 μm to obtain 196.4 g of water-absorbent resin particles (4). The water content of the water-absorbent resin particles (4) was 3.3% by mass. 0.1 parts by mass of amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) was mixed with 100 parts by mass of the water-absorbent resin particles to obtain a water-absorbent resin composition (6). The median particle size of the water-absorbent resin composition (6) was 167 μm, and the 30-second swelling height was 8.1 mm.
[0142] (Example 7)
[0143] 0.1 parts by mass of EDTMP·8H (2.3 μmol of EDTMP·8H per 1 g of water-absorbent resin particles) as a phosphonic acid chelating agent was added in a powder state to 100 parts by mass of the water-absorbent resin particles (2) obtained in Production Example 2, and the mixture was thoroughly mixed to obtain a water-absorbent resin composition (7). The median particle size of the water-absorbent resin composition (7) was 166 μm, and the 30-second swelling height was 15.3 mm.
[0144] (Example 8)
[0145] A slurry containing a hydrogel polymer 2 was prepared by the same method as in Production Example 2. The flask containing the slurry containing the hydrogel polymer 2 was immersed in an oil bath set at 125°C, and 103.5 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing the n-heptane, and 0.32 g of a 32% by mass aqueous solution of EDTMP·5Na (2.0 μmol of EDTMP·5Na per 1 g of water-absorbent resin particles) as a phosphonic acid chelating agent was added. Then, 2.76 g (0.317 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask, and the mixture was kept at 83°C for 2 hours. Then, the n-heptane was heated in an oil bath at 125°C to evaporate and dry, thereby obtaining 95.3 g of water-absorbent resin particles. The mixture was further passed through a sieve with a mesh size of 850 μm, thereby obtaining 69.3 g of a water-absorbent resin composition (8). The water content of the water-absorbent resin composition (8) was 3.2% by mass, the median particle size was 226 μm, and the 30-second swelling height was 15.2 mm.
[0146] (Example 9)
[0147] A slurry containing a hydrogel polymer 2 was prepared by the same method as in Production Example 2. The flask containing the slurry containing the hydrogel polymer 2 was immersed in an oil bath set at 125°C, and 103.6 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing the n-heptane, and 0.49 g of a 31% by mass DTPMP·7Na aqueous solution (2.2 μmol of DTPMP·7Na per 1 g of water-absorbent resin particles) was added. Then, 2.76 g (0.317 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask, and the mixture was kept at 83°C for 2 hours. Then, the n-heptane was heated in an oil bath at 125°C, evaporated, and dried to obtain 95.4 g of water-absorbent resin particles. The mixture was further passed through a sieve with a mesh size of 850 μm to obtain 71.3 g of a water-absorbent resin composition (9). The water content of the water-absorbent resin composition (9) was 3.3% by mass, the median particle size was 211 μm, and the 30-second swelling height was 13.0 mm.
[0148] (Example 10)
[0149] A water-absorbent resin composition (10) was obtained in the same manner as in Example 1 except that the amount of EDTMP·8H used was changed to 0.9 parts by mass (21 μmol of EDTMP·8H per 1 g of water-absorbent resin particles). The median particle size of the water-absorbent resin composition (10) was 179 μm, and the 30-second swelling height was 8.6 mm.
[0150] (Example 11)
[0151] A slurry containing the hydrogel polymer 1 was prepared by the same method as in Production Example 1. The flask containing the slurry containing the hydrogel polymer 1 was immersed in an oil bath set at 125° C., and 245.0 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing the n-heptane, and 2.57 g of a 32% by mass aqueous solution of ethylenediaminetetramethylenephosphonic acid pentasodium salt (abbreviated as EDTMP·5Na) as a phosphonic acid chelating agent (7.5 μmol of EDTMP·5Na per 1 g of water-absorbent resin particles) was added. Then, 7.15 g (0.821 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask, and the mixture was kept at 83° C. for 2 hours. Next, the n-heptane was heated in an oil bath at 125° C. to evaporate and dry, thereby obtaining 200.7 g of water-absorbent resin particles. The mixture was further passed through a sieve with a mesh size of 850 μm to obtain 197.3 g of water-absorbent resin particles (5). The water content of the water-absorbent resin particles (5) was 4.7% by mass. 0.1 parts by mass of amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) was mixed with 100 parts by mass of the water-absorbent resin particles to obtain a water-absorbent resin composition (11). The median particle size of the water-absorbent resin composition (11) was 176 μm, and the 30-second swelling height was 6.8 mm.
[0152] (Example 12)
[0153] A slurry containing the hydrogel polymer 1 was prepared by the same method as in Production Example 1. The flask containing the slurry containing the hydrogel polymer 1 was immersed in an oil bath set at 125° C., and 246.8 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing the n-heptane, and 5.13 g of a 32% by mass aqueous solution of ethylenediaminetetramethylenephosphonic acid pentasodium salt (abbreviated as EDTMP·5Na) as a phosphonic acid chelating agent (15 μmol of EDTMP·5Na per 1 g of water-absorbent resin particles) was added. Then, 7.15 g (0.821 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask, and the mixture was kept at 83° C. for 2 hours. Next, the n-heptane was heated in an oil bath at 125° C. to evaporate and dry, thereby obtaining 200.3 g of water-absorbent resin particles. The mixture was further passed through a sieve with a mesh size of 850 μm to obtain 194.6 g of water-absorbent resin particles (6). The water content of the water-absorbent resin particles (6) was 4.5% by mass. 0.1 parts by mass of amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) was mixed with 100 parts by mass of the water-absorbent resin particles that passed through the sieve with a mesh size of 850 μm to obtain a water-absorbent resin composition (12). The median particle size of the water-absorbent resin composition (12) was 185 μm, and the 30-second swelling height was 6.4 mm.
[0154] (Comparative Example 1)
[0155] A water-absorbent resin composition (13) was obtained by the same method as in Example 1 except that the amount of EDTMP·8H used was changed to 0.0001 parts by mass (0.0023 μmol of EDTMP·8H per 1 g of water-absorbent resin particles). The median particle size of the water-absorbent resin composition (13) was 179 μm, and the 30-second swelling height was 8.8 mm.
[0156] (Comparative Example 2)
[0157] A water-absorbent resin composition (14) was obtained by the same method as in Example 1 except that the amount of EDTMP·8H used was changed to 4.4 parts by mass (101 μmol of EDTMP·8H per 1 g of water-absorbent resin particles). The median particle size of the water-absorbent resin composition (14) was 178 μm, and the 30-second swelling height was 7.0 mm.
[0158] [Evaluation of water-absorbent resin particles]
[0159] (Determination of moisture content)
[0160] 2.0 g of water-absorbent resin particles are placed in an aluminum foil box (No. 8) that is pre-set to a constant weight (W1 (g)), the opening of the aluminum foil box is gently closed, and the total mass W2 (g) of the aluminum foil box containing the sample is accurately weighed. The aluminum foil box containing the sample is dried for 2 hours using a hot air dryer (manufactured by ADVANTEC, model: FV-320) with the internal temperature set to 200°C. The dried aluminum foil box containing the sample is cooled to room temperature in a desiccator. The total mass W3 (g) of the aluminum foil box containing the sample after cooling is measured. The moisture content of the sample is calculated by the following formula.
[0161] Moisture content [mass %] = {(W2-W3) / (W2-W1)} × 100
[0162] [Evaluation of water-absorbent resin composition]
[0163] (Measurement of median particle size (particle size distribution))
[0164] 5 g of the water-absorbent resin composition obtained in each manufacturing example was sieved using a sonic vibration sieve measuring device (Robot Shifter RPS-01, manufactured by Shinshin Enterprise Co., Ltd.), sieves with mesh sizes of 850 μm, 500 μm, 250 μm, 180 μm, 150 μm, 106 μm and 75 μm according to the JIS standard, and a tray. The mass of the particles remaining on each sieve was calculated as a mass percentage relative to the total amount. The mass percentage of the particles remaining on each sieve was accumulated in order from the particles with the largest particle size, and the relationship between the mesh size of the sieve and the cumulative value of the mass percentage of the particles remaining on the sieve was plotted on a logarithmic probability paper. By connecting the scattered points on the probability paper with a straight line, the particle size equivalent to the cumulative mass percentage of 50% was obtained, and it was taken as the median particle size of the water-absorbent resin composition.
[0165] (30-second swelling height measurement)
[0166] use Figure 1 The swelling height measuring device X shown measures the swelling height of the water-absorbent resin composition. Figure 1 The swelling height measuring device X shown in the figure comprises a moving distance measuring device 1, a concave circular cup 2 (45 mm in height, 90 mm in outer diameter, 40 mm in depth of the concave portion, 80 mm in inner diameter of the concave portion), a plastic convex circular cylinder 3 (79 mm in outer diameter, 60 through holes 7 with a diameter of 2 mm evenly arranged on the contact surface of the water-absorbent resin composition), and a nonwoven fabric 4 (weight per unit area 11 g / m 2The swelling height measuring device X can measure the displacement of the distance moved by the convex circular cylinder 3 in units of 0.01 mm using the laser 6. The concave circular cup 2 can evenly spread a predetermined amount of the water-absorbent resin composition. The convex circular cylinder 3 can evenly apply a load of 90 g to the water-absorbent resin composition 5 as a sample.
[0167] First, 0.2 g of the sample (water-absorbent resin composition 5) is uniformly spread in the concave circular cup 2, and a nonwoven fabric 4 is laid on it. Then, the convex circular cylinder 3 is gently placed on the nonwoven fabric 4, and the laser 6 of the sensor of the moving distance measuring device 1 is set to reach the center of the cylinder 3. Ion exchange water adjusted to 20° C. in advance is poured into the concave circular cup 2 through the through hole 7 of the convex circular cylinder 3 to swell the water-absorbent resin composition 5. The time when the laser senses that the water-absorbent resin composition 5 is swollen and the convex circular cylinder 3 is pushed up is regarded as the start of water absorption (0 seconds) (automatic measurement starts when a displacement of 0.5 mm occurs), and the distance (the displacement difference of the convex circular cylinder 3 in the direction perpendicular to the bottom surface of the concave part of the concave circular cup 2) by which the water-absorbent resin composition 5 is swollen and the convex circular cylinder 3 is pushed up is measured. The water level of the ion exchanged water was checked every 3 seconds from the start of the injection of the ion exchanged water, and the ion exchanged water was continuously injected intermittently so that the water surface was maintained at a height near the flat surface of the flat plate portion of the convex circular cylindrical body 3. 30 seconds after the moment when the water-absorbent resin composition 5 started to absorb water (more precisely, the moment when the water-absorbent resin composition absorbed a very small amount of ion exchanged water and the cylindrical body 3 was pushed up by 0.5 mm), the distance by which the convex circular cylindrical body 3 was pushed up (including the height (0.5 mm) by which the cylindrical body 3 was pushed up at the moment when the water absorption started) was recorded as the 30-second swelling height.
[0168] (Measurement of gel viscosity retention; evaluation of heat resistance)
[0169] The gel viscosity of the water-absorbent resin composition was measured by adjusting the temperature of the swollen gel to 25±0.5° C. using a Brookfield type rotational viscometer (Vismetron viscometer VDH2, manufactured by Shibaura Systems Co., Ltd., spindle rotor No. 5, rotation speed 10 rpm). The gel viscosity was measured in a state where the gel was placed in a 200 mL glass beaker with an inner diameter of 64 mmφ to a height of 65 mm.
[0170] 100 g of ion exchange water was added to a 200 mL beaker, and the mixture was stirred at 600 rpm using a magnetic stirring bar (cylindrical shape with a diameter of 8 mm × a length of 30 mm, without a ring). 2.0 g of the water-absorbent resin composition was added to the vortex generated by the stirring, and the mixture was stirred until the magnetic stirrer stopped due to the generated gel. This operation was performed twice in total to obtain a swollen gel equivalent to 4.0 g of the water-absorbent resin composition before swelling. Then, 200 g of the swollen gel thus obtained was immediately placed in a 250 mL glass heat-resistant bottle having a bottom outer shape of 70 mmφ and a mouth outer shape of 42 mmφ, and allowed to stand in a hot air dryer (manufactured by ADVANTEC, FV-320) at 90±2°C, and the viscosity of the swollen gel after 2 days and after 4 days was measured, and the gel viscosity retention rate S was calculated by the following formula (I), and this value was used as an index of heat resistance.
[0171] Gel viscosity retention rate S = B / A (I)
[0172] (In formula (I), A represents the gel viscosity after 2 days (mPa·s), and B represents the gel viscosity after 4 days (mPa·s))
[0173]
[0174] The evaluation results of the water-absorbent resin compositions obtained in each example and comparative example are shown in Table 1. It was confirmed that the water-absorbent resin compositions obtained in each example can maintain a good gel state under heating conditions of 90° C. This result shows that the water-absorbent resin compositions obtained in each example have excellent heat resistance in a swollen state, and can be said to be able to maintain a gel state for a long time even in an environment where a power cable is used or in an environment similar to it.
[0175] As described above, it is understood that the water-absorbent resin composition obtained in the examples has excellent heat resistance in a swollen state and can be suitably used as a waterproof material.
Claims
1. A water-absorbent resin composition comprising water-absorbent resin particles and a phosphonic acid chelating agent, The phosphonic acid chelating agent is contained in an amount of 0.01 to 40 μmol based on 1 g of the water-absorbent resin particles. 2 . The water-absorbent resin composition according to claim 1 , which has a 30-second swelling height of 6.0 mm or more.
3. A waterproof material comprising the water-absorbent resin composition according to claim 1 or 2.
4. A cable comprising the waterproof material according to claim 3.
Citation Information
Patent Citations
Water cut-off material and water cut-off method for underground cable with protective tube
JP2014147281A